Zdravljenje diseminiranega plazmocitoma z zdravilom bortezomib - Kodre, Veronika (Zdravniški vestnik, 2008)
Background In this retrospective study we evaluated effectiveness and safety of bortezomib, comparing our results with already published clinical studies. Methods Patients received bortezomib as part of everyday clinical practice andin the range of approved indications. We evaluated bortezomib effectivenessin 66 patients according to modified SWOG criteria and treatment responsiveness (CR, VGPR, PR, MR) or unresponsiveness (SD, PD). Treatment responsiveness was compared according to high risk (beta-2 microglobulin >= 5,5 mg/L) or standard risk (beta-2 mikroglobulin 65 ali 1) and previous treatment with thalidomid. Side effects and reasons for early treatment discontinuation were also evaluated. Results Patients received 1-7 previous treatments (median 1.5). Treatment responsiveness was observed in 80.3% patients (1.5% CR, 45.5 % VGPR, 21.2% PR and 12.1% MR). No statistical significant influence was observed according to: high risk (p = 0.178), age above 65 years (p = 0.756), > 1 previous treatment (p = 0.419) or previous treatment with thalidomid (p = 0.475). Side effects of bortezomib treatment were: anemia (40.9%), peripheral neuropathy grade 3 or more (28.7%), infections (21.2%), herpes zooster (12.1%), neutropenia (10.6%), trombocitopenia (9%) and gastro-intestinal problems (7.5%). Early discontinuation was observed due to: peripheral neuropathy (28.7%), other serious side effects (6%), bortezomib uneffectiveness (19.7%) or planned autologous transplant (15.1%). Conclusions Bortezomib (Velcade) is effective and safe treatment also for patients with multiple myeloma that developed resistance to previous treatments or belong to high risk patient group.
Keywords: Bence Jones Protein; Bence Jonesova beljakovina; Beta 2-Microglobulin; Beta 2-mikroglobulini; Drug Therapy; hematologija; Immunoglobulins; Imunoglobulini; Multiple Myeloma; Multipli mielom; plazmocitom; therapy; Treatment Outcome; zdravljenje; Zdravljenje, izid